A cross-sectional study of age differences and postural control in male athletes using the stability evaluation test (SET) - Williams, R. M.; Rice, T.; Lam, K.; McLeod, T. V. (International Journal of Athletic Therapy & Training, 2017)
Postural control is an integral part of sport participation and is often measured when assessing concussion and rehabilitating musculoskeletal injuries. The purpose of this study was to determine whether developmental differences in postural control, as measured by the Stability Evaluation Test protocol, exist between multiple male age groups (9-25-years-old). Significant differences were present across age groups, suggesting pediatric males demonstrated higher sway velocity scores than older males. We also found that preadolescent males showed increased postural sway when compared with older populations. Overall, it was found that age-related differences exist in postural control, with older males demonstrating less sway, and therefore better postural control.